Effects on Growth Performance Parameters, Carcass Traits, Meat Nutrimental Quality and Intramuscular Fatty Acid Profile of Rabbits Fed with Diets with Avocado Waste (Persea americana Mill) - Johana Paola Galeano-Díaz; Juan Edrei Sánchez-Torres; Ignacio Arturo Domínguez-Vara; Ernesto Morales-Almaraz; Javier German Rodríguez-Carpena; Fernando Grageola-Nuñez; Gema Nieto-Martinez (Agriculture, 2023)
The objective of this paper was to evaluate the effect of four levels (0%, 4.32%, 8.39% or 12.25%) of avocado waste (AW) included in the diets on productive performance, carcass characteristics and meat nutritional quality of fattening rabbits. For that, one hundred and twenty male rabbits (New Zealand × California; 945 ± 47 g initial body weight) were fed over 28 days, randomly distributed to one of the four treatments (T) (T1 = 0, T2 = 4.32, T3 = 8.39 and T4 = 12.25% AW as fed). The chemical and fatty acids profiles were evaluated in the Longissimus thoracis et lumborum (LTL) muscle. The rabbits fed with 8.39% of AW reported the best productive parameters (p < 0.05), the greater (p < 0.05) dissectible adipose tissue and higher polyunsaturated fatty acids (PUFAs) n-3 content (p < 0.05) than control meat. It is concluded that the inclusion of AW in the growing–finishing rabbit’s diet can modify the nutritional quality of the meat, reducing the n-6/n-3 ratio and the thrombogenic index.